KONTRIBUSI WISATA PERAIRAN BUKIT LAWANG TERHADAP SOSIAL EKONOMI MASYARAKAT DAN INDEKS KESESUAIAN WISATA DI KECAMATAN BAHOROK KABUPATEN LANGKAT SUMATERA UTARA The Contribution of Aquatic Tourism to Socioeconomic society and Tourism Sustainability index in - Azvi Mauriza Damanik; Yoes Soemaryono; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
The river is a stream of water across the surface of the earth and forming grooves or morphology stream water flow and has a good prospect to be developed as a nature tourist attraction. Langkatdistrict have a potential area into a tourist attraction that is Bukit Lawang.This study aims to determine the role of ecotourism related to socioeconomic, knowing the water quality associated with Capability Areas and Tourism Suitability Index, and knowing the strategy of sustainable management welfare of the public Bukit Lawang.This study Hwas held for one month, in January 2017 in the village of Bukit Lawang Bahorok Langkat District of North Sumatra.The results showed that the water qualityfor 6 parameters observed is good and in accordance with the carrying capacity of the region and can be seen in value to the activity of natural bath is 125 people / day,activity relaxing seating 240 people / day and rafting activities 105 / day as well as an index of conformity travel with the results of S2 (Match), the linkage with economic social travel the waters can be seen from the results of Return Cost Ratio R / C of value ≥ 1 where business mean to be positive and feasible to continue the effort lodging, souvenir shop, rafting guides, tire leasing, rental stalls except the restaurant business travel which results Benefit Cost Ratio B / C ≤ 1 means the business is worth negative and is not feasible to continue.Keywords: Bukit Lawang, Water Quality, Revenue, Return Cost Ratio R / C.